KONSEP AKHLAK DALAM KITAB ADABUL ALIM WAL MUTA’ALIM DAN IMPLEMENTASINYA PADA PEMBINAAN AKHLAK SANTRI - Fitria Salsabila; Nur Islamiyah; Aisyah Qurrotul Aini; Aida Nur Aini (JURNAL ILMIAH NUSANTARA, 2026)
. Adāb al-‘Ālim wa al-Muta‘allim, authored by Hadratussyaikh K.H. Hasyim Asy‘ari, is an important manuscript within the corpus of Islamic educational thought, particularly in the pesantren (Islamic boarding school) tradition. The work focuses on the cultivation of morals and ethics in the teaching–learning process. It was written as a comprehensive guide that elaborates in detail the manners (adab) that must be possessed by both educators (‘ālim) and students (muta‘allim).Broadly speaking, this book is divided into several chapters that discuss ethics across various dimensions, including: etiquette toward oneself (such as sincerity, purification of the heart, and maintaining proper conduct), etiquette toward teachers (respecting, serving, and being patient with them), etiquette toward knowledge (honoring books and avoiding complacency), and the etiquette of educators in the teaching process (being just, sincere, and providing good examples).The core message of this work is the emphasis that adab must precede knowledge. The process of seeking knowledge is not merely a transfer of cognitive information, but also an internalization of character values encompassing the affective and psychomotor domains. Its ultimate goal is to produce individuals who are knowledgeable, faithful, and of noble character. Although written in an earlier period, the concept of adab articulated in this book remains highly relevant as a response to moral and ethical degradation in contemporary education.